Mortality patterns in municipalities of a mining region before the Brumadinho dam failure, state of Minas Gerais, Brazil - Deborah Carvalho Malta; Gabriela Maciel dos Reis; Guilherme Augusto Veloso; Laís Santos de Magalhães Cardoso; Zulmira Maria de Araújo Hartz; Matthew Cunningham; Mohsen Naghavi (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To describe the patterns of overall mortality and mortality from external causes and the temporal evolution in the municipalities of the Paraopeba River Basin, before the socio-environmental disaster of the Brumadinho dam and, additionally, to investigate the correlation between mortality and socioeconomic deprivation in these municipalities. Methods: Global Burden of Disease Study mortality estimates for 26 municipalities in the state of Minas Gerais, Brazil, were analyzed. Rates of overall mortality and mortality from external causes were estimated in the triennia (T) T1 (2000 to 2002), T2 (2009 to 2011), and T3 (2016 to 2018). Pearson's correlation coefficient measured the association between mortality rates and socioeconomic deprivation, according to the Brazilian Deprivation Index (IBP). Results: There was a decrease in overall mortality in the Paraopeba River Basin from 717.7/100 thousand to 572.6/100 thousand inhabitants, and in most municipalities between T1-T3. Mortality from external causes increased from 73.3/100 thousand to 82.1/100 thousand, and it was higher in these municipalities compared with the mean for Brazil and Minas Gerais. Deaths from suicide and interpersonal violence increased from 29.6/100 thousand to 43.2/100 thousand in most of the 26 municipalities. Death rates due to unintentional injuries decreased during the period, and those due to transport injuries, increased. There was a positive correlation between socioeconomic deprivation and the percent change in mortality rates. Conclusion: Despite the strong presence of mining activity in the region, such did not reflect in the improvement of the sanitary situation. Death rates due to external causes increased in the period, associated with inequalities, which must be considered in the planning for the recovery of the disaster areas.